2001
DOI: 10.1143/jjap.40.1556
|View full text |Cite
|
Sign up to set email alerts
|

Jitter Analysis for Land/Groove Phase Change Disk

Abstract: The long-term performance of two active hydrogen masers developed at the National Measurement Laboratory of the CSIRO is presented. Six years of comparisons between the masers, the United States Naval Observatory (USNO) and the Bureau International des Poids et Mesures (BIPM) are summarized. Operating as independent clocks the masers showed outstanding long-term performance and consistently high weightings in the coordination of major time-keeping centres carried out by the BIPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Many studies on land-groove-type optical disks have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In this type of disk, crosstalk suppression is important for designing the groove structure. Therefore, the signal characteristics depending on the groove structure and their improvement methods have been widely studied for magnetooptical (MO) disks [4][5][6][7][8] and phase-change (PC) disks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on land-groove-type optical disks have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In this type of disk, crosstalk suppression is important for designing the groove structure. Therefore, the signal characteristics depending on the groove structure and their improvement methods have been widely studied for magnetooptical (MO) disks [4][5][6][7][8] and phase-change (PC) disks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the signal characteristics depending on the groove structure and their improvement methods have been widely studied for magnetooptical (MO) disks [4][5][6][7][8] and phase-change (PC) disks. [9][10][11] A video file system making a use of the landgroove-type magnetooptical disk had been proposed. 12) Further investigations of phase-change disks have been performed to increase the recording density, such as detailed simulation of signal mark formation on both the land and the groove 13) and UV laser mastering to realize a narrow track pitch.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phase-change materials have been commonly used in the recording layer of rewritable Blu-ray discs (BDs) and digital versatile discs (DVDs). [1][2][3][4][5] Marks on the phase-change recording layer of the optical disk are created at parts that are heated by a recording optical beam and are also quickly cooled by a heat sink layer adjacent to the recording layer. If marks are recorded using non-returnto-zero (NRZ) signals, the leading parts of long marks disappear.…”
Section: Introductionmentioning
confidence: 99%